Study of Clay Minerals in Venezuelan Plains Soils - SHRIVASTAVA, V.S.; ALFONSO, J.A.; BENZO, Z.; FLORES, S.; PAOLINI, J.E. (Asian Journal of Chemistry, 2010)
Clay minerals from soil samples were collected at different horizons from Savanna vegetation areas of Venezuela, which are known as Orinoco Llanos. The samples were settled and concentrated by the centrifuge method, for the extraction of clay. X-ray diffraction and scan electron microscopy analyses have been carried out for the samples. The analysis indicate that the clay samples contain mainly quartz (silica), illite and kaolinite minerals, while smectite was found in trace amount.